Even If AI Can Cure Loneliness - Should It? - Kiron, David; Unruh, Gregory (MIT Sloan Management Review, 2019)
AI devices that help stimulate psychological and physiological human connection are serving a population whose loneliness is at an all-time high, but they also raise societal concerns. And while it seems productive to solve technology-based loneliness with further technology, makers of social AI products and services need to consider whether their emotional connectors are worth the societal ramifications.